2021
DOI: 10.3390/cancers13061387
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Dose Rate Brachytherapy of Lip Carcinoma: Clinical Outcome and Quality of Life Analysis

Abstract: Purpose: Lip carcinoma represents one of the most common types of head and neck cancer. Brachytherapy is a highly effective therapeutic option for all stages of lip cancers. We report our experience of pulsed dose rate brachytherapy (PDR) as treatment of lip carcinoma. Methods and Materials: this retrospective single center study included all consecutive patients treated for a lip PDR brachytherapy in our institution from 2010 to 2019. The toxicities and outcomes of the patients were reported, and a retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Long-term side-effects include hypopigmentation, telangiectasias and in some cases a certain degree of fibrosis. However, these are very rare: over 90% of patients treated with HDRIB for LC have satisfactory functional and cosmetic results, and most patients who underwent the procedure would recommend it [ 8 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term side-effects include hypopigmentation, telangiectasias and in some cases a certain degree of fibrosis. However, these are very rare: over 90% of patients treated with HDRIB for LC have satisfactory functional and cosmetic results, and most patients who underwent the procedure would recommend it [ 8 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, to the best of our knowledge, no randomised studies comparing these different treatment strategies have been reported. In the clinic, the type of treatment modality is selected based on the size and location of the tumour, the expected functional outcome and the accessibility of the treatment type ( 11 ). The aims of the present study were to retrospectively evaluate the clinical profile and treatment outcomes of patients with SCC of the lip treated with radical intent at the Regional Cancer Centre.…”
Section: Introductionmentioning
confidence: 99%